Effects of L1-L2 congruency, collocation type, and restriction on processing L2 collocations - Jiang, Ying (Frontiers in Psychology, 2022)
Abstract The present study investigated the effects of L1-L2 congruency, collocation type, and restriction on L2 collocational processing. Advanced Chinese learners of English and native English-speaking controls performed an online acceptability judgment task to investigate how advanced L2 learners processed congruent (sharing the same meaning and structure in L1 language) collocations and English-only (not equivalent in L1 construction) collocations with the same node (right) word and a different collocate (left). The experimental materials included verb-noun (VN), adjective-noun (AN) collocations, free (less fixed), and restricted (more fixed) collocations chosen from BNC. The results revealed that: i) The non-native speakers were sensitive to L1-L2 congruency, but the native speakers were not. ii) The native speakers were sensitive to collocation restriction, whereas the non-native speakers were not. These results lend initial support to the mapping hypothesis and open choice principle of L2 collocational processing for Chinese English learners.